The Effect of The New Overtime System In Football On The Performance and Technical Parameters of The Teams - GÖK, Bilal (International Journal of Holistic Health, Sports and Recreation, 2023)
The aim of this study is to examine the effect of the new overtime system, which was started to be used with the 2022 World Cup and aims to add all of the ball out minutes to the end of the half, on the performance and technical parameters of the winning and losing teams in the world cup. In the tournament, 49 matches played in the group stage and after the group, whose normal time did not end in a draw, were discussed. The data used in the study were obtained from the official website of FIFA https://www.fifa.com. Statistical analysis of the obtained data was made with the IBM SPSS Statistics 24 package program. The determination of whether the data are suitable for normal distribution was made with the Shapiro Wilk test and it was observed that the data were normally distributed. According to this result, Independent Sample T test, which is one of the parametric tests, was applied in independent groups. According to the statistical results obtained, there was a significant difference between the two groups in the parameters of goals scored and shot on target (p<0.05). There was no significant difference between the two groups in passing, successful passing, ball handling, distance covered and high-intensity running parameters. As a result, it was determined that the teams in the matchs had close averages in the specified parameters, but the winning teams had higher averages of hits and goals. It can be said that the winning rate of the teams that shoot more in the matchs is higher. The fact that there is no significant difference in the total distance and high-intensity running between the teams can be interpreted as the tactically correct area and time should be covered on the basis of the team. In addition, the fact that the ball playing and passing parameters do not differ significantly can be interpreted as the teams playing the ball a lot or passing the ball a lot more result-oriented and passing more effectively.